2020
DOI: 10.1155/2020/8893653
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Activin A Serum Level and Carotid Intima-Media Thickness in Chronic Kidney Disease Patients

Abstract: Introduction. Chronic kidney disease (CKD) is associated with high mortality rates, mainly as a result of cardiovascular complications. Meanwhile, recent studies have suggested a role of a homodimer protein called activin A in chronic kidney disease-mineral and bone disorder (CKD-MBD) conditions that may exist in the vascular calcification and osteolytic process. Ultrasound examination of the carotid intima-media thickness (cIMT) is a noninvasive method to assess vascular calcification. This study aimed to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The available data only suggests the comparison of activin A levels in certain study groups with normal controls. [ 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…The available data only suggests the comparison of activin A levels in certain study groups with normal controls. [ 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Its serum levels increase early during CKD, before other bone markers, and correlate with bone turnover similar to intact PTH and FGF-23 [110]. Moreover, looking specifically at vascular calcification, in observational studies carotid intima-media thickness (cIMT), considered a clinical expression of the vascular calcification process, significantly correlated with Act-A serum levels, both in diabetes and CKD patients [111,112].…”
Section: Human Specimens and Clinical Studiesmentioning
confidence: 99%
“…In KT patients, previous studies have reported an increase in activin levels in allografts during ischemia-reperfusion injury and alternate macrophage activation (M2 phenotype) [17,18]. Furthermore, various studies have revealed the association of activin with inflammation, vascular calcification, and carotid intima-media thickness [19,20]. Hence, studies to improve anemia, bone mineral density, and abdominal aortic vascular calcification by inhibiting the activin pathway are in progress [21][22][23].…”
Section: Introductionmentioning
confidence: 99%